MENINGKATKAN PERILAKU MORAL ANAK MELALUI METODE BERCERITA BONEKA TANGAN PADA ANAK USIA 4-5 TAHUN DI KELOMPOK BERMAIN KEMBANG HARAPAN KAMPUNG BARU KECAMATAN GUNUNG TOAR KABUPATEN KUANTAN SINGINGI - ', Nurmas; ', Mahdum; ', Hukmi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract:. This study aims to determine the increase in moral behavior of children through a hand puppet storytelling in children aged 4-5 years. The number of subjects in this study were 12 children. The data collection techniques were used that observation. This study includes quantitative and qualitative research. Quantitatively, the data were analyzed descriptively percentage. Level changes measured by percent, while qualitatively explain the activities of children and teachers obtained through observation, interviews and performance during the study. The study hypothesis is the application of hand puppet storytelling method can improve the moral behavior of children aged 4-5 years. It can be seen from the analysis of the data obtained, before the given action (preliminary data) the average value of the child's moral behavior amounted to 40.97 Start Developing criteria (MB), and then after the first cycle with a hand puppet storytelling average experience an increase of 48.30 Developing criteria Start (MB). Improvement of cycle 1 is equal to 17.89%. Meanwhile, the activities of teachers in cycle 1 was the criterion Enough with the average value of 51.11. While the child's activities in cycle 1 earn a percentage of 42.22% with a sufficient criterion. Furthermore, after the second cycle increased to 78.32% Developing criteria Very Good (BSB). Improvement of cycle 2 of cycle 1 that is equal to 62.15%. While the activities of teachers in cycle 2 are the criteria for Good with an average value of 80%. While the child's activities in cycle 2 84.44% with criteria Good. Then to find out of that increase occurring in the cycle, the analysis of data beginning with cycle 2. From the data processing obtained an increase of 92%, this study should not be continued again for the next cycle.